Suitability of Electronic Nose as a Reflective Tool to the Measurement of Soil Fertility Factors - Lavanya, S.; Krishna Murthy, V. (Kathmandu University Journal of Science, Engineering and Technology, 2018)
Humic Acid (HA) and Fulvic Acid (FA) contribute prominently to soil fertility. They are aromatic in nature and hence can be determined by sensory array. This is apparently the first report on the employment of Electronic nose (E-nose) to detect HA and FA extracted from soil. The aim was to evaluate the E-nose sensor response to HA and FA chemically extracted from different agricultural soils. Humic acid and Fulvic acid were extracted from collected agricultural soils and the aroma was measured by E-nose from each of the seven soils. Their presence was confirmed by fluorescence spectroscopy. The Norm Aroma Index (NAI) was measured for: soil, soil after heat treatment, heat treated soil amended with extracted HA, heat treated soil amended with extracted FA, extracted HA and extracted FA. The NAI values were descending in the order: heat treated soil amended with extracted HA/FA, extracted HA/FA, soil (untreated) and heat treated soil. This indicates that HA and FA are detected by E-nose. It was also observed that the most sensitive sensors were 2, 3, 4, 8 and 5 for all agricultural soils tested. Out of the eight sensors in the sensory array of E-nose, above mentioned sensors consistently exhibited high response and these sensors when customized into a small unit may act as a soil fertility tester. Kathmandu University Journal of Science, Engineering and Technology Vol. 13, No. 2, 2017, page: 39-47